Developing international social capital: The role of communities of practice and clustering. Issue 2 (April 2019) - Urzelai, Berrbizne; Puig, Francisco
Highlights: Geographic communities of practice within clusters of compatriots create International social capital. Mechanisms based on informal and repeated interactions enable the access to local knowledge. Similar expatriates develop and use the community of practice and its social capital heterogeneously. Abstract: One criteria regarding where to invest in foreign markets is linked to the international social capital (ISC) that exists on the place, which enables the access to local knowledge and other location-specific advantages. There are alternative ways to create and make use of that ISC that are still unexplored by International Business literature. In this paper, we study the geographic communities of practice (CoP) that are formed by FDI firms from the same country-of-origin (the so-called country-of-origin clusters). For that purpose, the paper adopts a qualitative methodological approach through an inductive case study of expatriates from 13 Spanish subsidiaries co-located in China. Our findings suggest that there are particular mechanisms based on the informal connections and repeated interactions facilitated by a common language and non-competitive relationships that create an ISC in the CoP. Moreover, our analysis shows there is a heterogeneity in the way these mechanisms are developed and used by the member firms, and this is due to organizational and individual factors, as well as leadership dynamics. Our work contributes to Internationalization and Network theories by identifying unexplored mechanisms through which the ISC is developed at the host country level. Besides, it helps identifying competences (i.e. clustering competences) that help expatriate managers to be successful in their international assignments.